Accuracy and quality of immunization data in Iran: findings from data quality self-assessment survey in 2017 - Manoochehr Karami; Salman Khazaei; Abbas Babaei; Fatemeh Abdoli Yaghini; Mohammad Mehdi Gouya; Seyed Mohsen Zahraei (BMC, 2019)
Abstract Background The aim of this study was to assess the accuracy and quality of immunization data on the pentavalent (diphtheria, pertussis, tetanus, hepatitis B and Haemophilus influenzae type B (Hib)) and MMR vaccines as the administrative data of the expanded program on immunization (EPI) in Iran. Methods We conducted a Data Quality Self-assessment (DQS) survey from October to December 2017. Standardized DQS tools were used to assess the accuracy of reported immunizations data and quality of the immunization monitoring system at the provincial level of the healthcare system including health houses, health posts, rural and urban health centers and district health centers. Multistage cluster random sampling with proportional to size (PPS) weights was used to select target provinces and related health units. Accuracy ratio, quality index (QI), completeness and relevant quality indices of first dose of MMR (MMR1) and third dose of pentavalent vaccines were reported. Corresponding period of the survey was limited to reported administrative immunization data during the first 6 months of 2016. Results In relation to accuracy ratio, there was some evidence of under reporting of pentavalent (3rd dose) and MMR1 vaccines in health house units which were 100.94 and 101.1%, respectively. Completeness of reporting for both vaccines at different provincial levels was near 100%. However, the corresponding value for pentavalent (3rd dose) and MMR1 vaccines at the level of urban health centers was 96.67 and 94.17% respectively. Among the five components of a monitoring system data usage and core output had the lowest QI scores in either rural or urban as well as district healthcare centers. Conclusions Findings from our DQS survey reveals that administrative reporting of the immunization data was adequate at provincial and district levels of the healthcare centers. Although, addressing the existing concerns regarding timelines of the reporting by health authorities and staffs of EPI is warranted.